Health Seeking Behaviour During the COVID-19 Pandemic and Influencing Factors in Indonesia - Arif Kurniawan; Elviera Gamelia (Journal of Public Health and Pharmacy)
Introduction: Data from the Indonesian Ministry of Health on April 13, 2020, indicated that there were up to 4,557 positive COVID-19 cases in 34 provinces, 380 cases that recovered, and 399 cases that died. One of the transmissions of COVID-19 occurs through nosocomial infections that occur in health service institutions, namely hospitals, health centres’, or polyclinics. The significant incidence of nosocomial infection cases in the COVID-19 transmission chain raises the question of whether or not this alters community patterns around health service utilization. The objective of this research was to ascertain the community's health-seeking behavior during the COVID-19 epidemic and the elements that impact that behavior. The novelty of this research focused on the sociocultural context in Indonesia and its contributions to global discussions on pandemic health behavior.